Rancangan Sistem Pendaftaran Pasien (BPJS dan Umum) melalui Pengembangan Modul Sales ERP pada Odoo di Instalasi Kedokteran Nuklir - Salsabila Safitri; Ari Yanuar Ridwan; Umar Yunan Kurnia Septo Hediyanto; Kharisma Perdani Kusumahstuti (LPPM STIKOM Tunas Bangsa, 2023)
The registration process is the initial process to start the examination on all installations in each hospital. One hospital in Bandung alone can receive more than 200 patients per day, which of course can cause various problems, knowing also that all the registration processes that occur are still centralized. In the registration process, patients are divided into two types of patients: General and BPJS. With the central registration system, it raises several problems that occur in one of the Nuclear Medicine Installations at the Bandung public hospital, for example patient data that registers can only be accessed through the registration center which makes the Nuclear Medicine Installation service sector not yet have a system that contains a patient database, so the installation is still making a reporting system manually. The Nuclear Medicine Installation is also still not integrated between patient registration and examination and management of other systems. In this research, an Enterprise Resource Planning (ERP) system for General patient registration modules and BPJS will be developed using the open-source Odoo which will support patient registration management using the Quickstart method. The ERP system makes it easy for hospitals to design patient registration systems starting from the initial registration process, patient payments, to patient scheduling. The system will be tested functionally using integration testing and blackbox testing which will be validated by the Nuclear Medical Installation service department. The results of this study are the development of a general patient registration system and BPJS, as well as patient examination scheduling, and reporting related to patient registration